Equity option-implied probability of default and equity recovery rate - Bo Young Chang; Greg Orosi (Bank of Canada, 2016)
There is a close link between prices of equity options and the default probability of a firm. We show that in the presence of positive expected equity recovery, standard methods that assume zero equity recovery at default misestimate the option-implied default probability. We introduce a simple method to detect stocks with positive expected equity recovery by examining option prices and propose a method to extract the default probability from option prices that allows for positive equity recovery. We demonstrate possible applications of our methodology with examples that include large financial institutions in the United States during the 2007-09 subprime crisis.
Keywords: G13; G33; 330; Asset pricing; Financial markets; Market structure and pricing